Phytochemical Screening of Calotropis procera Flower Extracts and Their Bio-Control Potential on Culex sp. Mosquito Larvae and Pupae - Azmathullah, N.Md. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Mosquito larvicidal efficacy and phytochemical screening of aqueous and ethanol extracts of the flowers of Calotropis procera, a common weed plant were evaluated in the present study, Phytochemical screening of the flower extracts of C.procera indicated the presence of alkaloids, carbohydrates, saponins, phenols, tannins, terpenoids and flavanoids which are known to possess medicinal and pesticidal properties. Larvicidal effects of the flower extracts of C.procera on the fouth instar larvae and pupae of Culex sp., which transmits filariasis to humans was investigated. Results revealed a dose and time dependant effect of the extracts on mosquito larvae with 5% extract concentration causing 100% mortality within 3days exposure. Culex sp. pupae were more resistant to the flower extract compared to the fourth instar larvae indicating differential susceptibility of mosquito life stages. The potential use of C.procera extract as an effective eco-friendly, bio-control agent against mosquito larvae is discussed